THE ROLE OF MODERN COMPUTER TECHNOLOGIES IN THE DIAGNOSIS AND TREATMENT OF NEUROLOGICAL DISORDERS IN ADOLESCENTS - Atakhanov Sanjarbek Anvarovich; Xayrullaeva Durdona Xayrullo qizi; Rasulova Farzona Gʻayratjon qizi (Bright Mind Publishing, 2025)
This article discusses the possibilities and prospects of creating facilities for doctors using modern computer technologies for the identification, correct diagnosis and treatment of neurological disorders in adolescents.
Keywords: MRI, autism, EEG, epilepsy, Parkinson's syndrome, computed tomography.